Shape-selective separation of geraniol and nerol via noncovalent interactionswith β-cyclodextrin. Issue 1 (2nd January 2016) - Yang, Zu-Jin; Zhou, Dan; Fang, Yan-Xiong; Ji, Hong-Bing
Abstract: In this paper, selective separation of the isomeric compounds geraniol and nerol, based on the preferential affinity of β-cyclodextrin (β-CD) for geraniol was investigated. To demonstrate the potential application of β-CD for separation of geraiol from nerol, the structure of the inclusion complexes was characterized with various physico-chemical techniques. The selective noncovalent binding property of β-CD was confirmed by quantum-chemical calculations. For the mixture, which contains 50 wt% of geraniol and nerol, respectively, 96% of geraniol in complex can be obtained, and the similar separation efficiency was found after use for three times.